Design Cooling Load on Economy Passenger Train Type K3-438 using Thermodynamic Physics - Diyajeng Luluk Karlina; Choirul Mufit (LPPM Universitas Andalas, 2024)
Abstract— Factors that influence comfort on trains are thermal comfort factors. Thermal comfort is a thermal interaction between humans and their surroundings that satisfies the human mind. The principle of thermal comfort itself is related to the surrounding body temperature. Because if the human body temperature and the environment have a significant temperature difference, discomfort will occur. Research aims to design an effective air conditioning system to produce a better air supply so that it can overcome the problem of thermal comfort in trains. The first methodology for this research was collecting primary and secondary data. Primary data includes data on train size, construction, type of equipment, and number of passengers. While secondary data is data on design conditions. To determine the value of the cooling load, it is necessary to analyze the heat load in the train which includes sensible heat load and latent heat load. The results of this research obtained a total sensible heat value of 86371.19 Btu/hr. And the total latent heat is 73855.839 Btu/hr. Based on the results of research that has been carried out, it can be Conclusions were drawn from the calculation of the cooling load on the Type K3-438 Passenger Train with a capacity of 94 passengers. It was concluded that the minimum cooling load required was 40412.48 kcal/hr. Keywords: Cooling Load, Thermal Comfort, Passenger Train, Thermodynamic Physics